Household responses to information on child nutrition: Experimental evidence from Malawi - Emla Fitzsimons; Bansi Malde; Alice Mesnard; Marcos Vera-Hernández (Institute for Fiscal Studies (IFS), 2012)
This paper provides evidence on household responses to the relaxation of one barrier constraining adoption of health practices - lack of information - in a resource constrained setting. It examines the effects of a randomized intervention in Malawi which provides mothers with information on infant nutrition and health. It finds that the intervention results in increases in household food consumption, particularly of protein-rich foods by children. The increased household consumption is funded by increased father's labor supply, constituting evidence that changes in the perceived child health production function affect adult labor supply. Improved consumption also results in better child health.
Keywords: D10; I15; I18; O12; O15; 330; Infant Health; Health Information; Cluster Randomized Control Trial; Ernährungspolitik; Mütter; Informationsversorgung; Ernährung; Kinder; Gesundheit; Malawi